PENGARUH STRES KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN UNIVERSITS AL – IRSYAD CILACAP - Nuni Wulansari; Rizqi Zulqornain; Muhammad Fahmi Z; Fajar Nur Wibowo (Pusat Riset dan Inovasi Nasional, 2022)
This study aims to analyze the effect of work stress and work environment on the performance of employees of the University of Al - Ersyad Cilacap. The object of this research is the University of Al - Ersyad Cilacap, while the subjects are employees of the University of Al - Ershad Cilacap. This research uses sampling with purposive sampling technique. The number of samples in this study were 169 respondents. Data were obtained through questionnaires which were distributed directly to employees of Al-Irsyad University, Cilacap. The data analysis technique uses SPSS version 22. Based on the results of the analysis performed, it shows that work stress affects employee performance and the work environment affects employee performance.